Non-toxic Nodular Goiter Causing Compression of Adjacent Structures (Revista de Medicina Clinica, 2022)
Clinical Snapshot on Non-Toxic Nodular Goiter Originating Compression of Adjacent Structures presented in Volume 6 Issue 3 of the Revista de Medicina Clínica.
Keywords: Non-Toxic Nodular Goiter; Compression; Neck